Serum ferritin and transferrin saturation levels in β0 and β + thalassemia patients - Estevão, I. F. [UNESP] (2011)
There have been few studies on the mutations that cause heterozygous beta-thalassemia and how they affect the iron profile. One hundred and thirty-eight individuals were analyzed, 90 thalasemic β0 and 48 thalasemic β+, identified by classical and molecular methods. Mutations in the hemochromatosis (HFE) gene, detected using PCR-RFLP, were found in 30.4% of these beta-thalassemic patients; heterozygosity for H63D (20.3%) was the most frequent. Ferritin levels and transferrin saturation were similar in beta-thalassemics with and without mutations in the HFE gene. Ferritin concentrations were significantly higher in men and in individuals over 40 years of age. Transferrin saturation also was significantly higher in men, but only in those without HFE gene mutations. There was no significant difference in the iron profile among the β0 and β+ thalassemics, with and without HFE gene mutations. The frequency of ferritin values above 200 ng/mL in women and 300 ng/mL in men was also similar in β0 and β+ thalassemics (P > 0.72). Our conclusion is that ferritin levels are variable in the beta-thalassemia, trait regardless of the type of beta-globin mutation. Furthermore, HFE gene polymorphisms do not change the iron profile in these individuals. ©FUNPEC-RP www.funpecrp.com.br.